Competitive effect of dopant concentration and the size of the nanorods over the electron phonon coupling in Cd doped ZnO nanorod arrays. (January 2021) - Brahma, Sanjaya; Lee, Ping-Han; Chen, Hsin-Hung; Lee, Alex Chinghuan; Huang, Jow-Lay
Abstract: Earlier reports on resonance Raman scattering in ZnO suggests that the electron phonon coupling in ZnO usually increase with nanoparticle size or decline with the doping concentration. We investigated the effect of combination of the concentration of dopant and the variation of size of nanorods over the electron phonon interaction in Cd doped ZnO nanorod array fabricated by a simple, low temperature (90 °C) growth process. The resonant Raman measurement revealed minor decrease in the electron phonon coupling strength as defined by the intensity ratio (I2LO /I1LO ) at low doping concentration (20 mol %) and increase at high Cd concentration (>20 mol %) confirming a strong dependence of electron phonon coupling strength on the concentration of dopant. The enhancement in the electron phonon coupling strength at high doping concentration was due to the increase in the diameter of the nanorod rather than the concentration of dopants explaining the competitive effect of dopant and size over the electron phonon interaction in a range of doping concentration. The Cd doping led to the decrease in the band gap and the increase (decrease) in the intensity of the excitonic emission (visible luminescence) as observed by the photoluminescence property. X-ray, Fourier transform infrared (FTIR) analysis confirmed low temperature doping of Cd at the tetrahedral coordination site of the ZnO lattice Although, the Cd concentration in the growth solution was systematically varied from 1 mol % to 80 mol %, the maximum Cd doping varied from 3 at. % (80 mol %) at the surface to 0.2 at % - 0.6 at. % in the bulk after surface cleaning by Ar ion etching. Highlights: Investigation of the electron phonon interaction in Cd doped ZnO nanorod array. Competitive effect of dopant and size of the nanorod over the electron phonon coupling strength. Dopant induced enhancement in the near band edge excitonic emission. Gradation of Cd doping concentration from surface (3 at. %) to bulk (0.6 at. %). Simple, low temperature (90 °C) growth of Cd doped ZnO nanorods and a detailed analysis.